Determinan Pemanfaatan Program Kesehatan Preventif pada Kelompok Pekerja Informal : Scoping Review - Sarasyita Nada Re; Ayun Sriatmi; Sri Winarni (Jurnal Ners, 2026)
Background Informal workers represent a highly vulnerable group due to limited access to preventive health services. Various individual, social, economic, policy, and environmental factors contribute to their low participation in preventive health programs. Objective This study aims to identify the determinants of preventive health service utilization among informal workers based on a review of 13 national and international journals published between 2021 and 2025. Method A systematic review approach was applied by examining relevant articles from international and national databases. The analysis included socio-demographic variables, employment status, health insurance policies, and environmental factors influencing access to preventive services. Results Education, health knowledge, attitudes, and family support were found to enhance preventive health service utilization. Economic constraints such as unstable income and lack of social security emerged as major barriers. Furthermore, distance to health facilities, service quality, and limited availability of health professionals exacerbated access disparities, making informal workers more vulnerable to chronic diseases. Conclusion Preventive health service utilization among informal workers is influenced by a combination of individual, social, economic, policy, and environmental factors. Inclusive policies, community-based interventions, and improved health infrastructure are required to increase participation and ensure equitable access to preventive health services. Keywords: informal workers, preventive health, determinants, social security, health access